Nestin-containing cells express glial fibrillary acidic protein in the proliferative regions of central nervous system of postnatal developing and adult mice - Wei, L.-C; Shi, M; Chen, L.-W; Cao, R; Zhang, P; Chan, Y.S (Brain research. Developmental brain research, 2002)
We are interested in the expression patterns of nestin, an embryonic intermediate filament that represent a neural precursor marker, in the mammalian central nervous system. With an immunohistochemical approach, distribution of nestin-containing cells and their colocalization with glial fibrillary acidic protein (GFAP) or neuronal nuclear specific protein (NeuN) were studied in adult and postnatal days 2–30 (P2–30) mice. Nestin-immunoreactivity was predominately distributed in certain proliferative regions, such as cerebral cortex, hippocampus, hypothalamus, subfornical organ, cerebellar cortex, area postrema, midline raphe glial structures, as well as ependymal and subependymal zones of the brain and spinal cord. The majority of nestin-immunoreactive cells, characterized by astroglial profiles of multiple and radial processes, showed a partial overlapping distribution with that of GFAP-immunoreactive astroglial cells. Double immunofluorescence confirmed that about 77% of these nestin-immunoreactive cells exhibited GFAP-immunoreactivity, indicating that a large percentage of nestin-expressing cells may have committed to astroglial cells. In developing mice, down-regulation of nestin expression was observed between P7 and P14. Although co-expression of nestin and NeuN occurred in cortical neurons of P2–7 mice, nestin-containing cells showing NeuN-immunoreactivity disappeared in CNS in older animals. Our results reveal the distribution pattern of nestin-containing neural precursors in the postnatal CNS and provide evidence on their differentiation fate to neurons and astrocytes, suggesting that nestin-containing glial cells may play an important role in remodeling and repairing in the postnatal and adult central nervous system.